Cold-Sprayed Metal Coatings with Nanostructure - Shuo Yin; Chaoyue Chen; Xinkun Suo; Rocco Lupoi (Advances in Materials Science and Engineering)
Cold spray is a solid-state coating deposition technology developed in the 1980s. In comparison with conventional thermal spray processes, cold spray can retain the original properties of feedstock, prevent the adverse influence on the underlying substrate materials, and produce very thick coatings. Coatings with nanostructure offer the potential for significant improvements in physical and mechanical properties as compared with conventional non-nanostructured coatings. Cold spray has also demonstrated great capability to produce coatings with nanostructure. This paper is aimed at providing a comprehensive overview of cold-sprayed metal coatings with nanostructure. A brief introduction of the cold spray technology is provided first. The nanocrystallization phenomenon in the conventional cold-sprayed metal coatings is then addressed. Thereafter, focus is switched to the microstructure and properties of the cold-sprayed nanocrystalline metal coatings, and the cold-sprayed nanomaterial-reinforced metal matrix composite (MMC) coatings. At the end, summary and future perspectives of the cold spray technology in producing metal coatings with nanostructure are concluded.